Special Considerations in Social Network Interviewing and Mapping with Vulnerable Populations. Issue 4 (November 2021) - Smith, Melissa E.; Pahwa, Rohini
This short take describes the process of enhancing social network interviews with qualitative inquiry to facilitate participant recall, contextualize participant–alter relationships, and increase cultural responsiveness with populations with cognitive impairments. The authors illustrate this process, including the use of a qualitative interviewing name generator, with an example of a mixed-methods project exploring community experiences with adults with serious mental illnesses.